Ethnobotany of traditional vegetables used by Sama-Bajau community in Kota Belud, Sabah, and phytochemical and anti-aging investigation of crassocephalum crepidioides - Ag Kanak, Fadzilah (2021)
Recording of traditional knowledge (TK) on ethnobotany could be a useful tool to discover new alternative for antioxidant and anti-aging agent from local vegetables. The objectives of this study were: to record ethnobotany of traditional vegetables (ulam) as aging prevention materials, to investigate phytochemical, antioxidant, and anti-aging content of Crassocephalum crepidioides, to determine the anti-aging activity and postulate the efficacy of the selected C. crepidioides extracts (CCE) against the effect of induced UVB radiation in human dermal cells line (HSF1184). TK were qualitatively evaluated using semi-structured interviews with six informants. A total of 46 species of traditional vegetables from 41 genera and 25 families were recorded. The informants believed eating ulam would provide them with nutrition and as functional food for anti-aging. Jaccard’s index of similarity for ulam species between Kampung Taun Gusi and Kampung Menunggui was J = 0.348. In average, informants cited 7.67 ± 3.89 vegetable taxa, and there was no significance difference (paired t-test, two tailed (α = 0.05, d.f.= 2) = 4.30, p > 0.05) between genders and knowledge on traditional vegetables (ulam). Distilled water, hot water, and ethanol crude extracts of C. crepidioides (CCE) were tested for total phenolic content (TPC) (Folin-Ciocalteu method), total flavonoid content (TFC) (aluminium chloride colorimetric method), and three antioxidant assays (DPPH scavenging, ABTS decolourization, and FRAP assays). The identification of phytochemical compound was analyzed using High Performance Liquid Chromatography method (HPLC), which revealed the presence of polyphenols, namely, chlorogenic acid, epicatechin, and rutin. Gas Chromatography Mass Spectrometry (GCMS) analysis of ethanol extract revealed 44 phytocompound. Ethanol extract has shown higher TPC (175.06 ± 0.574 μg/ml) and TFC (139.72 ± 0.923 μg/ml) compared to water extracts. Anti-aging efficacy of CCE was further evaluated in fibroblast dermalcell line (HSF1184), which was induced for photodamage using UVB radiation and hydrogen peroxide. Findings revealed that at lower concentration CCE water extracts exhibited no cytotoxicity at lower concentration (≤ 200 μg/ml) on proliferation of tested dermal cells line (HSF1184). Meanwhile for ROS scavenging assay in fibroblast cell line, hot water extract has shown the higher scavenging 49.64% ± 3.77% at 250 μg/ml treatment, compared to distilled water extract (39.66% ± 10.82%) and ethanol extract (18.69% ± 4.44%) at the same concentration. The inhibition of elastase by CCE were found at concentration range of 0-100 μg/ml. Collagen content of UV induced cells were observed increased after treated with various concentration (0-100 μg/ml) of CCE. The traditional claim of obtaining anti-aging and antioxidant benefits from eating ulam were scientifically validated in this work.